Amorphous Al1-xTix, Al1-xVx, and Al1-xFex phases in the hydrogen cycled TiCl3, VCl3 and FeCl3 enhanced NaAlH4 systems - Pitt, M.; Vullum, P.; Sørby, M.; Emerich, H.; Paskevicius, Mark; Buckley, Craig; Gray, E.; Walmsley, J.; Holmestad, R.; Hauback, B. (Elsevier B.V., 2012)
The twice hydrogen (H) cycled planetary milled (PM) and cryo milled (CM) NaAlH4 + xTMCl3 (transition metal (TM) = Ti, V, Fe) systems (x > 0.1) have been studied by high resolution synchrotron X-ray diffraction, and high resolution transmission electron microscopy (TEM). Intense primary amorphous (a-) Al1−xTMx halos are evident in diffraction data of PM samples for V and Fe, and in CM samples for Ti, V, and Fe. Weaker primary amorphous Al1−xTix halos are evident in PM samples for Ti. The Ti poor a-Al1−xTix phase observed for NaAlH4 + xTiCl3 (x > 0.1) ranges in composition from a-Al86.5Ti13.5 → a-Al92Ti8. High resolution TEM studies of the Al1−xVx phases in the H cycled PM NaAlH4 + 0.1VCl3 system demonstrates that a nanoscopic composite morphology can exist between face centred cubic (fcc) crystalline (c-) Al1−xVx and a-Al1−xVx phases, with the c-Al1−xVx/a-Al1−xVx composite embedded on the NaAlH4 surface. The amorphous Al1−xVx reaches ca. 28 at.% V.